Indonesian Netizen Reponse to Covid-19 Vaccine News in Instagram IDN Times - Annisa Nurul Izmi; Hajrah Hajrah; Andi Agussalim Aj (INSIGHT: Indonesian Journal Social Studies and Humanities, 2021)
Abstract. This study aims to analyze the comments of Indonesian netizens in responding to the Covid-19 vaccine news using the Discourse Analysis theory by Teun A. Van Dijk, but focused on analyzing the dimensions of the text which consists of three parts, namely macro structure, superstructure and micro structure. This type of research is qualitative with a descriptive design. The data on the written comments of Indonesian netizens who responded to news related to the Covid-19 vaccine shared on Instagram IDN Times. The primary data source was obtained from Instagram on one of the national mainstream media portal accounts, namely IDN Times which reported on the Covid-19 vaccine. The results of this study indicate that netizens in the IDN Times Instagram comment column tend to be against the Covid-19 vaccine. Netizens who are against vaccines interpret vaccines as a government business field and are dangerous, while netizens who are pro-vaccine interpret vaccines as being able to increase immunity so they can protect themselves and those around them. The text of netizen comments is easy to understand even though they use non-formal language. The vocabulary of terms used by netizens is also easy to understand and used to find communication between people. The emphasis of the message used by netizens is that they tend to use all capital letters in one sentence or some of their vocabulary. Keywords: Netizen, Vaksin Covid-19, Analisis Wacana